Adoption of Social Media during Covid-19 Pandemic by African Presidents: A Cross-Sectional Study of Selected Facebook Accounts - Adikpo, Janet Aver (Sage Publications Inc, 2023)
This paper examined the adoption of social media to disperse information at the beginning of the ongoing coronavirus pandemic. Content analysis was employed to identify and select relevant posts for presidents of five African countries (Egypt, South Africa, Democratic Republic of Congo, Ethiopia, and Nigeria) from February to July 2020, which were analyzed using descriptive statistical methods. Results indicate that African leaders utilized Facebook mostly in April, posting majorly in text form about issues centered on diplomatic ties, information and orientation, and preventive measures. Followers were more inclined to share the posts than they react by emojis and comments based on Facebook account, post form, and post topic. The findings demonstratively uphold the significance of social media in leadership communication, highlighting ways by which frequent and dominant content can be directed in messages during a crisis.
Keywords: leadership communication; social media; Facebook; African leaders; Covid-19 pandemic